X-ray micro-laminography for the ex situ analysis of W-CFC samples retrieved from JET ITER-like wall. (21st January 2016) - Tiseanu, I; Craciunescu, T; Lungu, M; Dobrea, C
Abstract: x-ray micro-laminography was qualified and implemented as a complementary solution for the 3D microstructural analysis of tungsten coated carbon-fibre reinforced carbon (W/CFC) samples retrieved from JET ITER-like wall. As expected, the W layers spatially correlate with the morphology of the CFC substrate. Three main cases were distinguished; (i) tungsten layers coated parallel to PAN fibre bundles tend to have a quasi-continuous, weakly waved surface (waves amplitude <100 μ m); (ii) tungsten layers coated onto the relatively porous felt region appear to smoothly follow even the surface of the largest pores of around 250 μ m and (iii) samples coated perpendicular to the PAN fibre bundles display frequently and strong crater-like discontinuities of the metal layer. The characteristics dimensions of these gaps range in the order of 300–400 μ m both in the coating plane and perpendicular to it. On some craters the bottom W layer is broken and the generated debris can be found even deeper than one mm into the CFC substrate. These W particles, sized of 20–40 μ m, are always found in the large gaps located between the fibre bundles perpendicular to the coated surface.